Primary Health Care Technicians in the learning processes - Miranda Monar, Erika Elba; Cajamarca Alvarado, Martha Elizabeth (Revista Minerva, 2022)
In the present work the authors leave a referential study on the use of digital resources in the teaching of Chemistry, seeking to delve into a topic that, although it is not new, allows us to address a topic of great importance today, the teaching of a discipline school how Chemistry should always be accompanied by all the tools that from the point of view of science and Didactics are necessary for effective learning, precisely the work to seek to capture which are some of these tools that allow this type of development.